Diet composition and seasonal feeding patterns of a freshwater ringed seal (Pusa hispida saimensis) - Auttila, Miina; Sinisalo, Tuula; Valtonen, Mia; Niemi, Marja; Viljanen, Markku; Kurkilahti, Mika; Kunnasranta, Mervi
2015